1994
DOI: 10.1180/claymin.1994.029.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Stability constants for silicate adsorbed to ferrihydrite

Abstract: A B ST R ACT: Intrinsic surface acidity constants (Kal intr, Ka2 imr) and surface complexation constant for adsorption of orthosilicate onto synthetic ferfihydrite (Ksi for the complex -=FeOSi(OH)3) have been determined from acid/base titrations in 0.001-0.1 M NaCIO4 electrolytes and silicate adsorption experiments in 0.01 M NaNO3 electrolyte (pH 3-6). The surface equilibrium constants were calculated according to the two-layer model by Dzombak & Morel (1990). Near equilibrium between protons/hydroxyls in solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 27 publications
3
54
0
1
Order By: Relevance
“…Several researchers have observed that the presence of dissolved silica species can inhibit or promote the formation of different mineral phases (Anderson and Benjamin, 1985;Hansen et al, 1994;Mayer and Jarrell, 1996). We therefore expect to see qualitative disparities in the precipitates formed in Columns 1 and 3 compared to the silica-fed Columns 2 and 4.…”
Section: Precipitate Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Several researchers have observed that the presence of dissolved silica species can inhibit or promote the formation of different mineral phases (Anderson and Benjamin, 1985;Hansen et al, 1994;Mayer and Jarrell, 1996). We therefore expect to see qualitative disparities in the precipitates formed in Columns 1 and 3 compared to the silica-fed Columns 2 and 4.…”
Section: Precipitate Characterizationmentioning
confidence: 97%
“…(Klausen et al, 1995;Sivavec and Horney, 1997;Erbs et al, 1999;Williams and Scherer, 2001;Lee and Batchelor, 2002a,b;O'Loughlin et al, 2003). The presence of dissolved silica species has been shown (Anderson and Benjamin, 1985;Hansen et al, 1994;Mayer and Jarrell, 1996) to alter the types of iron (hydr)oxide phases that may form. A shift in precipitate identity to less redox active phases or phases with fewer sorption sites could potentially reduce PRB efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Stumm and colleagues were among the pioneers, who elaborated a ligand-exchange model to explain and predict the adsorption of H 4 SiO 4 on goethite [8]. Other authors [10,19,20] have used but also developed this ligand-exchange model. Very recently, Hiemstra et al modelled silicate sorption onto goethite from 1.0 × 10 −4 to 1.0 × 10 −3 mol L −1 solutions using a modified surface complex model (CD-MUSIC distribution model) [21].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, the study of interaction between silicate and iron oxides as well as other minerals was mainly carried out by batch adsorption experiments, modeling methods, and ex situ spectroscopy techniques [1,3,7,[10][11][12]. However, there are very few if any in situ studies on the sorption of silicate species onto magnetite showing the formation of surface complexes with time.…”
Section: Introductionmentioning
confidence: 99%